Molecular Detection of blaOXA-51 in Carbapenem-resistant Acinetobacterbaumannii Isolated from Different Clinical Sources (Medico Legal Update, 2020)
Carbapenems are the drugs of choice against serious infections caused by Gram-negative bacteriaCarbapenem-resistant. Acinetobacterbaumannii (CRAB) represents one of the important causing agentsof nosocomial infections especially in immunocompromised and Intensive Care Units (ICUs) patients. Theaim of this work was to identify the Carbapenem-Resistant genes in Acinetobacterbaumannii isolated fromBaghdad and Ramadi hospitals. Among 48A. baumannii isolates, 33 isolates (68.75%) were resistant toimipenem and meropenem. One gene for carbapenem resistance (blaOXA-51 like) were amplified by PCR.The presence of blaOXA-51-like genes in 100% of CRAB isolates indicated that the blaOXA-51-like genesare the predominant mechanism for imipenem resistance in our isolates.